INTEGRATING PRIVATIZATION, DIGITAL HEALTH, AND SUSTAINABILITY: A HYBRID FRAMEWORK FOR HEALTHCARE TRANSFORMATION UNDER SAUDI ARABIA’S VISION 2030 (Lex localis - Journal of Local Self-Government, 2025)
Saudi Arabia’s Vision 2030 is reshaping healthcare through a dual emphasis on privatization and digital transformation, with sustainability positioned as a critical enabler of long-term resilience. This paper proposes and evaluates a hybrid framework where public–private partnerships (PPPs) finance and operationalize digital health adoption while embedding equity and environmental standards. The analysis benchmarks Saudi reforms against global leaders such as Singapore, Switzerland, and Estonia, as well as regional peers in the Gulf, positioning the Kingdom as a unique hybrid model. Empirical illustrations—including dialysis service privatization, the Seha Virtual Hospital, and insurance reforms—demonstrate how financing structures, digital integration, and sustainability initiatives are converging in practice. Policy recommendations highlight structuring PPP contracts with digital and environmental clauses, insurer-driven incentives for preventive care, and robust monitoring frameworks. Collectively, the study underscores Saudi Arabia’s potential to emerge as a global exemplar of healthcare transformation that is efficient, equitable, and future-proof.